Clinico-pathological profile of scrub typhus in children: a cross sectional study from Eastern India - Dasgupta, Rayan; Basu, Sumita; Mukherjee, Asha (International Journal of Contemporary Pediatrics, 2021)
Background: Scrub typhus is a vector-borne zoonosis, endemic in Asia and it may present as an undifferentiated fever or with multisystem involvement. This study was carried out to understand the varied presentation of scrub typhus in children and the response to treatment in a tertiary care hospital in Eastern India. Methods: All children between 1 month and 12 year of age admitted with fever for more than 5 days and positive IgM ELISA for scrub typhus were included in the study and their course in hospital was documented. They were randomly divided into 2 groups of 41 patients each, into doxycycline and azithromycin group and were then evaluated for therapeutic response. Results: In this study, pallor (89%) was the commonest finding followed by hepato-splenomegaly (73.2%), pneumonia (65.9%) and rash was found in 43.9%. Eschar was found in 32.9% whereas serious complications like shock and meningoencephalitis was found in 9.8%. Pericardial effusion was detected in 23.2% cases, coronary artery dilatation in 11% cases and both effusion as well as coronary artery dilation was found in 2.4%. In azithromycin group, 73.2% patients had drug response whereas in doxycycline group, 92.7% patients had drug response and this association was statistically significant (p=0.0188). Two patients who presented late with shock expired but all others responded to treatment and were doing well on follow up. Conclusions: Scrub typhus may present with multisystem involvement including cardiac manifestation which needs to be identified early by echocardiography. Doxyclycine is still the best modality of treatment and if used early, outcome is favourable.